IMPLEMENTASI MANAJEMEN KELAS DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK - Sayuti; Nurul Asma (Jurnal Tarbiyah Almuslim, 2023)
This research aims to determine the application of classroom management in increasing students' interest in learning in class This research uses a field research approach (Field Research), namely data collection is carried out in the field. The nature of this research is qualitative descriptive research. The research findings inform: That the inhibiting factors for the implementation of classroom management in increasing interest in learning for class student learning is reduced. The solutions to overcome this problem include: by arousing students' interest in learning through the application of varied learning models, providing learning media such as occasionally learning using focus so that students' interest in learning increases, and trying to create a comfortable and enjoyable classroom atmosphere for students